1987
DOI: 10.1007/bf00270679
|View full text |Cite
|
Sign up to set email alerts
|

Collicular involvement in a saccadic colour discrimination task

Abstract: We have recorded the neural activity of single superior colliculus (SC) neurons in monkeys engaged in a saccadic target/nontarget discrimination task based on a colour cue. Since correct execution of this task probably depends on cortical signal processing, our experiments are of interest for getting a better insight in the problem of how cortical and subcortical signals, relevant for the visual guidance of saccades, are combined. The experiments were designed to distinguish between two extreme possibilities: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 34 publications
4
28
0
Order By: Relevance
“…This seems to imply that distractor-evoked inhibition is sensitive to the location of the distractor. Physiological and anatomical evidence (Johnson and Everling 2006;Krauzlis et al 2004;McPeek and Keller 2002a;Ottes et al 1987) is consistent with both location-specific and broad inhibition. For example, Johnson et al (2006) found that, during an antisaccade task, DLPFC neurons sent input that was assumed to be inhibitory to the colliculus in which prosaccades were programmed.…”
Section: Novelties and Predictionsmentioning
confidence: 63%
“…This seems to imply that distractor-evoked inhibition is sensitive to the location of the distractor. Physiological and anatomical evidence (Johnson and Everling 2006;Krauzlis et al 2004;McPeek and Keller 2002a;Ottes et al 1987) is consistent with both location-specific and broad inhibition. For example, Johnson et al (2006) found that, during an antisaccade task, DLPFC neurons sent input that was assumed to be inhibitory to the colliculus in which prosaccades were programmed.…”
Section: Novelties and Predictionsmentioning
confidence: 63%
“…Traditionally, experiments in SC were performed with single spots of light as targets for saccades. More recently, recordings of SC neurons occur in the presence of more complex stimulus displays that include targets and distractors (Ottes et al, 1987;Glimcher and Sparks, 1993;Basso and Wurtz, 1998;Edelman and Keller, 1998;McPeek and Keller, 2002;Port and Wurtz, 2003). The stimulus displays are sometimes adopted from those used in psychophysical experiments designed to explore visual search (Treisman and Gelade, 1980;Egeth and Yantis, 1997;Schall and Thompson, 1999;Palmer et al, 2000;Wolfe and Horowitz, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As the magnocellular pathway is not colour opponent and so does not carry colour information, this renders the SC insensitive to colour (Marrocco & Li 1977). Although colour-opponent saccade-related activity can develop within the SC under appropriate circumstances, the initial sensory response of neurons is non-opponent (Ottes et al 1987). Therefore, it should be possible to abolish all direct visual input to the SC-whether it be from the retina or from the cortex-by using appropriately selected coloured targets.…”
Section: Introductionmentioning
confidence: 99%